2020
DOI: 10.46300/91016.2020.7.9
|View full text |Cite
|
Sign up to set email alerts
|

Fault Detection and Classification for Slider Attachment Process using Convolution Neural Network

Abstract: Hard Disk Drive (HDD) utilizes automation machines for the assembly processes used in the industry to achieve higher production rates and lower costs. The Head Gimbal Assembly (HGA) production process has two main parts: glue dispensing and slider attaching by an Auto Core Adhesion mounting Machine (ACAM). The slider attaching process produces a mounted head to the suspension utilizing vacuum pressure to hold and position a slider. The errors from a vacuum leak from any step trigger system alarms resulting in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The Convolution Neural Network (CNN) was applied to detect the fault on the mount head surface in the slider attachment process. The result demonstrated that CNN could be used to classify the fault condition by using image data [1]. High-Speed automation machines are widely used in HGA production process, therefore Fault Tolerant Control (FTC) utilizing PI servo with observer was used to increase the reliability of the machine control system [2].…”
Section: Introductionmentioning
confidence: 99%
“…The Convolution Neural Network (CNN) was applied to detect the fault on the mount head surface in the slider attachment process. The result demonstrated that CNN could be used to classify the fault condition by using image data [1]. High-Speed automation machines are widely used in HGA production process, therefore Fault Tolerant Control (FTC) utilizing PI servo with observer was used to increase the reliability of the machine control system [2].…”
Section: Introductionmentioning
confidence: 99%